The effect of ethanol extract of soursop leaf (Annona muricata L.) on Adhesion of Streptococcus mutans ATCC 35668 to hydroxyapatite discs - Friska Ani Rahman; Tetiana Haniastuti; Trianna Wahyu Utami (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
The demineralization of dental hard tissues can be caused by dental plaque. Dental plaque contains various components, especially bacteria attached to the extracellular matrix. Streptococcus mutans (S. mutans) has extracellular glucan as adhesin that is important in the attachment mechanism of tooth surface. The natural substance can be used for preventing plaque formation by inhibiting the attachment of S. mutans. Soursop plant has been used in treating various diseases. The leaves of the soursop (Annona muricata L.) are used as a material to inhibit potential attachment of bacteria S. mutans. Common surfaces that is used in adhesion testing is hydroxyapatite (HA). The aim of this study was to evaluate the effect of ethanol extract of soursop leaf (EESL) on the adhesion of S. mutans ATCC 35668 to HA discs. Soursop leaves were extracted by the maceration method using 70% ethanol. The experiment was carried out by analyzing the inhibition adhesion of S. mutans ATCC 35668 on HA discs after incubation with different concentrations of soursop leaf extract. The concentrations of extract tested were: 150; 125; 100; 75; and 50 mg/ml. Chlorhexidine 0.2% was used as a positive control while DMSO 5% was used a negative one. Data were evaluated by One Way Anova. This study statistically showed significant differences of S. mutans colony count between groups (p<0.05).The results of a post hoc Dunnett T3 test showed that the 2 highest concentrations of extract (125 and 150 mg/ml) reduced S. mutans adhesion on HA discs.The obtained results showed that ethanol extract of soursop leave inhibits the adherence of S. mutans to the HA disc.